Investigations of selected physical properties of graphite oxide and thermally exfoliated/reduced graphene oxide in the aspect of their applications in photonic gas sensors - Drewniak, Sabina; Pustelny, Tadeusz; Muzyka, Roksana; Stolarczyk, Agnieszka; Konieczny, Grzegorz (Photonics Letters of Poland, 2015)
In this work, the results of measurements of two sensing materials: graphite oxide and thermally exfoliated/reduced graphene oxide are presented. The changes of resistance were registered in the changing atmosphere (modified concentration of hydrogen). Authors also try to explain the reasons for different response of the samples on the identical external conditions, by measuring the samples by means of the Differential Scanning Calorimetry (DSC) technique. Full Text: PDF References S. Paszkiewicz, A. Szymczyk, Z. Spitalsky, J. Mosnacek, Z. Rosłaniec, "Struktura i właściwości termiczne nanokompozytów ekspandowany grafit(EG))/poli(tereftalan etylenu)(PET)", Chemik 66(1), (2012)- in polish DirectLink H. Kim, A. A. Abdala, C. W. Macosko, "Graphene/Polymer Nanocomposites", Macromolecules 43(23), (2010) CrossRef S. Stankovich, D. A. Dikin, R. D. Piner, K. A. Kohlhaas, A. Kleinhammes, Y. Jia, Y. Wu, S. T. Nguyen, R. S. Ruoff, "Synthesis of graphene-based nanosheets via chemical reduction of exfoliated graphite oxide", Carbon 45(7), (2007) CrossRef C. H. A. Wong, O. Jankovsky, Z. Sofer, M. Pumera, "Vacuum-assisted microwave reduction/exfoliation of graphite oxide and the influence of precursor graphite oxide", Carbon 77 (2014) CrossRef R. R. Nair, H. A. Wu, P. N. Jayaram, I. V. Grigorieva, A. K. Geim, "Unimpeded permeation of water through helium-leak-tight graphene-based membranes", Science 335 (2012) CrossRef T. Pustelny, J. Ignac-Nowicka, B. Jarzabek, A. Burian, "Optical investigations concerning layered metalphthalocyanine nanostructures affected by NO2", Optical applicata vol. 34(4), 5510561 (2004) DirectLink S. Drewnak, T. Pustelny, M. Setkiewicz, E. Maciak, M. Urbańczyk, M. Procek, Z. Opilski, J. Jagiello, L. Lipinska, "Vibrational Spectroscopy of H2O by Lie Algebraic Methods", Acta Physica Polonica A 124(3), (2013) CrossRef T. Pustelny, M. Setkiewicz, S. Drewniak, E. Maciak, A. Stolarczyk, M. Urbańczyk, M. Procek, K. Gut, Z. Opilski, I. Pasternak, W. Strupinski, "The sensibility of resistance sensor structures with graphene to the action of selected gaseous media", Bull. Pol. Ac.: Tech. 61(2), (2013) DirectLink L. Lipińska, R. Koziński, J. Jagiełło, K. Librant, M. Aksienionek, Z. Wiliński, "Grafen płatkowy", Chemia Przemysłowa 5 (2012) C. Yao, J. Ren, C. Liu, T. Yin, Y. Zhu, L. Ge, "Hydrogel Improved the Response in the Titania/Graphene Oxide One-Dimensional Photonic Crystals", ACS Appl Mater Interfaces 6(19), (2014) CrossRef G. Sobon, J. Sotor, J. Jagiello, R. Kozinski, M. Zdrojek, M. Holdynski, P. Paletko, J. Boguslawski, L. Lipinska, K. M. Abramski, "Graphene Oxide vs. Reduced Graphene Oxide as saturable absorbers for Er-doped passively mode-locked fiber laser", Optics Express 20(17), (2012) CrossRef A. D. Dobrzanska-Danikiewicz, D. Lukowiec, D. Cichocki, W. Wolany, "Carbon nanotubes decorating methods", Archives of Materials Science and Engineering 61(2), (2013) DirectLink Patent US 2798878. DirectLink Ł. Smędowski, R. Muzyka, "Grafen – metody otrzymywania a zastosowanie i właściwości", Karbo 2, 128 (2013)- in polish Ch. Zhang, W. Lv, X. Xie, D. Tang, Ch. Liu, Q.-H. Yang, "Towards low temperature thermal exfoliation of graphite oxide for graphene production", Carbon 62, 11 (2013) CrossRef S. Drewniak, T. Pustelny, R. Muzyka, G. Konieczny, P. Kałużyński, "The effect of oxidation and reduction processes of graphite on physicochemical properties of graphite oxide and reduced graphene oxide", Photonics Letters of Poland, 6(4), 130 (2014) CrossRef